Symptomatic treatment of infantile nystagmus: a systematic review - Li, Xuanwei; Huurneman, Bianca; Goossens, Jeroen (Frontiers in Neuroscience, 2025)
Infantile nystagmus (IN) is a neuro-ophthalmic condition characterized by involuntary rhythmic eye movements that manifest early in childhood. The surge of recent articles focusing on the treatment of IN demonstrates the need for a new systematic review of the intervention options. The diverse causes of IN complicate its differentiation from symptoms secondary to other conditions, presenting challenges for clinical decision-making and systematic review. This study provides the first extensive, focused summary of symptomatic treatment options for IN. We noted that current approaches can be broadly categorized into four types of interventions: surgical, pharmacological, optical, and perceptual training methods, each offering distinct benefits and limitations. Most of the included studies (28/52) focused on invasive surgical interventions. Alternatively, the nascent perceptual training showed promising improvements in both visual acuity (VA) and quality of life (QoL). Heterogeneous reporting of treatment outcomes for IN hindered meta-analysis and precise comparison of intervention effects, underscoring an urgent need for standardized outcome measures in future studies. We further suggest including functional vision measurements and QoL assessments to better address patient well-being, rethinking invasive surgical approaches and exploring non-invasive treatment modalities in clinical practice.